Exploratory analysis of the potential disconnect between objective inflammatory response and clinical response following certolizumab pegol treatment in patients with active axial spondyloarthritis - Filip van den Bosch; Martin Rudwaleit; Helena Marzo-Ortega; Natasha de Peyrecave; Victoria Navarro-Compán; Lars Bauer; Rachel Tham; Thomas Kumke; Mindy Kim (RMD Open)
Introduction This post hoc analysis evaluated the relationship between objective measures of inflammation and clinical outcomes following 12 weeks of certolizumab pegol (CZP) treatment in patients with active axial spondyloarthritis (axSpA).Methods We report the proportion of patients achieving ≥50% and ≥75% improvements in clinical composite outcome measures of disease activity (Axial Spondyloarthritis Disease Activity Score [ASDAS], Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]) and objective measures of inflammation (C reactive protein [CRP], Ankylosing Spondylitis spine MRI score [ASspiMRI-a] Berlin score and Spondyloarthritis Research Consortium of Canada [SPARCC] MRI Sacroiliac Joints [SIJ] score) following 12 weeks of CZP treatment. Data from two independent readers over four MRI reading campaigns were pooled using a mixed model with repeated measures for each variable.Results 136 patients (radiographic axSpA [r-axSpA]: 76; non-radiographic axSpA [nr-axSpA]: 60) were included. Following CZP treatment, CRP, ASspiMRI-a Berlin score and SPARCC SIJ score were reduced by ≥50% in most patients (CRP: 136/136 [100.0%]; Berlin: 73/136 [53.7%]; SPARCC SIJ: 71/136 [52.2%]), and often by ≥75%. Less than half of patients with r-axSpA and nr-axSpA showed ≥50% reduction in clinical responses (BASDAI: 64/136 [47.1%]; ASDAS: 66/136 [48.5%]). These results were also observed at the individual patient level; ≥50% improvements in MRI/CRP inflammatory measures did not translate into similar improvements in clinical responses for most patients.Conclusion There is a potential disconnect between objective measures of inflammation and clinical outcome responses in patients with axSpA. The use of only clinical response measures as trial endpoints may underestimate anti-inflammatory treatment effects.Trial registration number NCT01087762.